The long-term outcomes of the Anderson-Kestenbaum procedure - Kuziel, Jeffrey; Pope, Hannah; Kothapalli, Aishwarya J.; Larson, Scott A.; Drack, Arlene; Dumitrescu, Alina V. (Frontiers in Ophthalmology, 2023)
Introduction Nystagmus is an involuntary, conjugated, rhythmic movement of the eye that can be idiopathic or secondary to ocular or neurologic pathologies. Patients with nystagmus often have a position of gaze in which their symptoms are dampened or absent, referred to as the “null zone.” The Anderson-Kestenbaum procedure is a bilateral recess-resect procedure of the four horizontal rectus muscles which aims to bring the null position into the primary gaze. This study aims to further elucidate long-term outcomes and factors associated with optimal postoperative outcomes. Methods Patients with a diagnosis of nystagmus and a surgical code for strabismus between June 1990 and August 2017 were considered for inclusion in the study. Patients were included if they had undergone the Anderson-Kestenbaum procedure and had follow-up lasting at least 24 months post-operatively. Data collected included demographic information, characteristics of the nystagmus, underlying etiology of nystagmus, and pre-and post-operative measurements. Results 25 patients were included. At their last recorded follow-up, 44% of patients achieved an optimal surgical outcome -an abnormal head position of 10 degrees or less. 88% of patients showed an overall improvement in their head posture at the last follow-up. The absence of an abnormal head position at the visit closest to 24 months post-operatively was found to be significantly associated with the lack of a significant head position at the last follow-up visit. Optimal surgical outcomes were not significantly associated with the underlying diagnosis, the direction of the abnormal head position, or the type of nystagmus. Discussion The relatively long follow-up of this cohort allows this study to further elucidate the long-term outcomes of the Anderson-Kestenbaum procedure. Overall, our results suggest that although improvement in head position post-operatively is likely, it is still expected that many patients will have a residual abnormal head position after the procedure. The results of this study are helpful in counseling patients, especially knowing that if they do not have a significant head position at 24 months follow-up, they are unlikely to develop one. However, due to the small sample size, larger cohorts and more standardized follow-up may provide further insight into the procedure’s outcomes.